2010
DOI: 10.1007/s11199-010-9878-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender Stereotypes Depicted by Western and Korean Advertising Models in Korean Adolescent Girls’ Magazines

Abstract: Using content analysis based on Goffman's (1979) typology, the authors examined gender role stereotypes in Korean fashion magazines targeting adolescent girls. Korean women were more stereotypically portrayed than any other group as smiling, pouting, and with a childlike or cute expression. On the other hand, Western women were more stereotypically portrayed than any other group in the categories of licensed withdrawal and body display. In some categories, male models were more female-stereotypically portrayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…McLaughlin and Goulet (1999) found that Goffman's categories were rare in American magazines aimed at African-Americans, with half of the advertisements classified as 'other' . Nam, Lee, and Hwang (2011), found that several Goffmanian categories did not occur in Korean girl's magazines. Moreover, Korean male portrayals were more in accordance with conventions considered feminine in American studies.…”
Section: Gender Representation: Poses Power and The Persistence Of Dmentioning
confidence: 99%
“…McLaughlin and Goulet (1999) found that Goffman's categories were rare in American magazines aimed at African-Americans, with half of the advertisements classified as 'other' . Nam, Lee, and Hwang (2011), found that several Goffmanian categories did not occur in Korean girl's magazines. Moreover, Korean male portrayals were more in accordance with conventions considered feminine in American studies.…”
Section: Gender Representation: Poses Power and The Persistence Of Dmentioning
confidence: 99%
“…It has also been reported that adolescent girls get pleasure from reading teen magazines, which, in addition to other types of media, affect the adolescent girls by communicating messages about ideal beauty and stereotypical gender roles (Radway, 1991;Ballentine & Ogle, 2005;Nam, Lee & Hwang, 2011). Studies have also been conducted on the effect of teen magazines on adolescent girls' beauty perception and consumption habits in general (McRobbie, 1993;Gonick, 1997;Duke & Kreshel, 1998;Gane, 2007;Kim et al, 2011), and in different countries around the world (Silvestre, 2009;Chen & Jackson, 2012;Nam, et al, 2011). Most of the results of these studies suggest that a western beauty standard that characterizes women as thin, blueeyed, blonde, and with an upturned nose, is promoted globally in women's and adolescent girls' magazines.…”
Section: )mentioning
confidence: 99%
“…Using a sample of recent Chinese print ads, this study contributes to the body of research on gender portrayals in advertising of nonWestern countries (e.g., Arima 2003;Nam et al 2011). It also provides insight into how (1) Working roles…”
Section: Discussion and Limitationsmentioning
confidence: 97%
“…Western women were shown in higher levels of nudity (Huang and Lowry 2012), more likely to be shown in the Sensual/Sexy beauty type (Cheng and Frith 2006), in seductive dress (Frith et al 2004), in revealing clothes or as nude (Nam et al 2011) than local Asian models. Overall, Western women in Asian advertising are stereotyped as sexual or physically attractive in ads that are "body" oriented (Frith et al 2004;Johansson 1998, Zhou andBelk 2004).…”
Section: Western Women As Symbols Of Status and Universal Beautymentioning
confidence: 99%
See 1 more Smart Citation